Factors Influencing the Behavioral Intention to Perform Breast Self-Examination in Young Indonesian Adolescents - Nur Hafizhah; Tanjung Anitasari Indah Kusumaningrum (Jurnal Ilmu Kesehatan Masyarakat)
In Indonesia, breast cancer has the highest incidence among all cancer types. The high prevalence of breast cancer cases in adult women. Breast Self-Examination (BSE) is a crucial method for early breast cancer detection. This research aimed to determine the factors that influence the intention of young women aged 15-20 years to carry out BSE behavior in the Penumping Surakarta Health Center Work Area. This research used a cross-sectional approach. The research was carried out in March – April 2024. The sampling technique used quota sampling on 140 young women aged 15-20. Data analysis used the Chi-square test and multiple logistic regression test. The research results showed that there was a relationship between attitude (p-value = 0.001), subjective norms (p-value = 0.001), and perceived behavioral control (p-value = 0.002) to carry out BSE behavior. Attitude was a higher predictor factor in young women's intention to do BSE (p-value = 0.022; OR = 6.1; 95% CI (1.3-28.9). Attitude and perceived behavioral control significantly influence young women’s intention to engage in BSE. Young women with a positive attitude towards BSE are 6.1 times more likely to perform BSE compared to young women who have a negative attitude. We recommend health workers at the Penumping Community Health Center implement health promotion to enhance positive attitudes toward BSE among young women.